Negotiation for newcomers: how to license in an academic library - Geuther, Christina (My University, 2014)
With increasing demands of electronic collections in academic libraries, there is more to manage in licensing that inevitably affects Fair Use. Librarians need to be aware of terms that limit this conventional interpretation while negotiating authorized use and users. Negotiation for Newcomers breaks down how to use model licenses, creating checklists for comparing a license to policy, and the negotiation process. Some key terms and their examples are also highlighted. This poster was presented at the 2014 Kansas Library Conference in the Academic Library category.
Keywords: Electronic resources; Licensing; License negotiation; Academic libraries